Immunosenescence Study of T Cells: A Systematic Review - Rodriguez, Ivon Johanna; Lalinde Ruiz, Nicolás; Llano León, Manuela; Martínez Enríquez, Laura; Montilla Velásquez, María del Pilar; Ortiz Aguirre, Juan Pablo; Rodríguez Bohórquez, Oscar Mauricio; Velandia Vargas, Esteban Alejandro; Hernández, Edgar Debray; Parra López, Carlos Alberto (Frontiers in Immunology, 2021)
Background: Aging is accompanied by alterations in immune response which leads to increased susceptibility to infectious diseases, cancer, autoimmunity, and inflammatory disorders. This decline in immune function is termed as immunosenescence; however, the mechanisms are not fully elucidated. Experimental approaches of adaptive immunity, particularly for T cells, have been the main focus of immunosenescence research. This systematic review evaluates and discusses T cell markers implicated in immunosenescence. Objective: To determine the best flow cytometry markers of circulating T cells associated with immunosenescence. Methods: We systematically queried PubMed, MEDLINE, EBSCO, and BVS databases for original articles focused on two age groups of healthy humans: 18–44 (young adults) and >60 (older adults) years. In accordance with the Cochrane methodology, we synthesized data through qualitative descriptions and quantitative random effects meta-analysis, due to extensive heterogeneity. Results: A total of 36 studies conducted in the last 20 years were included for the qualitative analysis and four out of these studies were used to perform the meta-analysis. A significant decrease in naïve T cell subset was observed in older adults compared to young adults. Primary markers used to identify senescent cells were loss of CD28 and increased expression of CD57 and KLRG1 in terminally-differentiated memory T cell subset in older adults. Moreover, we observed an increase in proinflammatory cytokines and decrease in telomere length in old adult T cells. It was not possible to perform quantitative synthesis on cell markers, cytokines, and telomere length because of the significant variations between the groups, which is attributed to differences in protocols and unreported measurements, thus generating a high risk of bias. Conclusions: Heterogeneity among studies in terms of data report and measurement techniques and high risk of bias were major impediments for performing a robust statistical analysis that could aid the identification of eligible flow cytometry markers of immunosenescence phenotype in T cells.